2017
DOI: 10.1002/psp.2096
|View full text |Cite
|
Sign up to set email alerts
|

“On the move, or staying put?” An analysis of intrametropolitan residential mobility and ageing in place

Abstract: Population ageing and urbanisation are worldwide phenomena that are transforming societies and having profound economic and social effects on cities and countries throughout the world.Ageing is not taking place evenly, and in many developed cities, ageing growth rates are greater in peripheral areas than in the centre. This paper determines how intrametropolitan residential mobility and ageing-in-place patterns vary across age categories and geographical scales, explored through a case study of metropolitan Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 99 publications
1
14
0
Order By: Relevance
“…In general, two of the most influential theoretical perspectives on residential mobility are the life-cycle and life course models (Atkins, 2018). In the life-cycle model residential mobility is a functional response to major life transitions, particularly family transitions (Clark & Withers, 2002), such as cohabitation, the transition to parenthood, and changes in household size.…”
Section: Residential Mobilitymentioning
confidence: 99%
“…In general, two of the most influential theoretical perspectives on residential mobility are the life-cycle and life course models (Atkins, 2018). In the life-cycle model residential mobility is a functional response to major life transitions, particularly family transitions (Clark & Withers, 2002), such as cohabitation, the transition to parenthood, and changes in household size.…”
Section: Residential Mobilitymentioning
confidence: 99%
“…The first, from the urban informatics field, involves the use of data to measure effects on residential mobility or outcomes. This includes using objective indicators such as population, economics, and transportation (e.g., travel time and distance to work) [31]; land use and transportation accessibility [32]; the distance between residential areas and infrastructure [33]; health status [34]; population and population aging; poverty [35]; and income level [36]. Studies using these indicators have the advantage of explaining population movement between cities by way of long-term case studies, and such research has been conducted in multiple cities.…”
Section: Subjective Indicators For the Evaluation Of Neighborhood Envmentioning
confidence: 99%
“…In recent years, the concept of ‘ageing in place’ has been attracting a growing academic interest (Atkins, 2018; Smetcoren et al, 2017). Ageing in place has been defined as ‘the desire and tendency of older persons to stay in their current dwelling units for as long as possible’ (Pynoos et al, 2007, p. 711).…”
Section: Introductionmentioning
confidence: 99%
“…As such, it has been argued that ageing in place can enhance a sense of independence, identity, autonomy, security, and emotional attachment with the dwelling and neighbourhood (e.g., Kendig et al, 2012; Pynoos et al, 2007; Wiles et al, 2012). However, some long‐cherished home environments may ultimately become unsuitable for the needs of older adults (Atkins, 2018; Han & Kim, 2016; Judd et al, 2014). Several studies have demonstrated possible hazards and negative outcomes for the independence, health and wellbeing of older people when living in inadequate housing (Golant, 2011; Lord et al, 2006; Oswald et al, 2007; Sixsmith & Sixsmith, 2008; Wagner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%